METTL3-mediated m6A modification regulates D-galactose-induced skin fibroblast senescence through miR-208a-5p - Huang, Gaoxiang; Sun, Sainan; Liao, Mingde; Wang, Jing; Yan, Qing; Li, Jing; Meng, Yi; Wang, Qi; Guo, Zhen; Tan, Jiyong; Li, Jing (Frontiers in Immunology, 2025)
IntroductionAs the most abundant epitranscriptomic modification, N6-methyladenosine (m6A) critically influences aging and age-related pathologies. However, its regulatory interplay with microRNAs (miRNAs) in skin aging remains poorly defined.MethodsAging phenotypes were recapitulated using D-galactose (D-gal)-induced senescence models in mouse skin fibroblasts (MSFs) and mice. Interventions included METTL3 overexpression/knockdown, miR-208a-5p mimic/inhibitor transfection, and pharmacological mitophagy induction (GSK). Molecular analyses assessed m⁶A dynamics, gene regulation, and mitochondrial function.ResultsIn D-gal-induced aging models, global RNA hypomethylation and reduced METTL3 expression were observed, while METTL3 overexpression attenuated cellular senescence. Mechanistically, METTL3 depletion elevated miR-208a-5p levels via YTHDF2-mediated m⁶A recognition, establishing epitranscriptional control. This upregulated miR-208a-5p directly targeted the 3'-UTR of OPA1 (optic atrophy type 1), suppressing mitophagic activity. Critically, senescent phenotypes induced by METTL3 knockdown or miR-208a-5p mimicry were reversed by pharmacological mitophagy induction (GSK), confirming mitochondrial homeostasis as the pathway's functional nexus.DiscussionThese results establish an m6A-dependent METTL3/miR-208a-5p/OPA1 axis that regulates mitophagy and skin aging. Pharmacological rescue of mitophagy highlights this pathway's therapeutic relevance for age-related dermatopathology.